Test of the Ability of Fluorescent Pseudomonas to Dissolve Phosphate - Norman, Mayanda; Advinda, Linda; Chatri, Moralita; Handayani, Dezi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Phosphate is a vital nutrient required for plants, yet its presence in the soil is frequently limited due to being held by specific ions. Microorganisms that solubilize phosphate, particularly fluorescent Pseudomonas, are considered among the most efficient agents for phosphate solubilization. This research intends to assess the capacity of six fluorescent Pseudomonas isolates derived from the rhizosphere of different plants to solubilize phosphate, and to analyze their IKF values. The research was carried out descriptively from June to August 2025 at the Plant Physiology Laboratory, Faculty of Mathematics and Natural Sciences, Padang State University. Observations were conducted by noticing the development of clear zones and determining the IKF values. The findings indicated that every isolate, specifically PfPj1, PfS36, PfLAHP2, PfCas, PfS31, and PfKd7, was capable of solubilizing phosphate. The highest IKF value was found in isolate PfKd7 (4.91), whereas the lowest was recorded for PfS36 (4.08). Variations in IKF values indicate differences in the capacity of each isolate to release organic acids, which are involved in the phosphate solubilization process. This discovery reinforces the capability of fluorescent Pseudomonas as an eco-friendly biological agent to enhance phosphorus availability.